Age-Stratified T Cell Responses in Children Infected with Mycobacterium tuberculosis - Dreesman, Alexandra; Corbière, Véronique; Dirix, Violette; Smits, Kaat; Debulpaep, Sara; De Schutter, Iris; Libin, Myriam; Singh, Mahavir; Malfroot, Anne; Locht, Camille; Mascart, Françoise (Frontiers in Immunology, 2017)
Tuberculosis (TB) in young children differs from adult TB in that the risk of rapid progression to active TB (aTB) is higher in children than in adults. The reasons for this increased risk are not fully understood. Early differentiation remains difficult between children at risk to develop aTB from those who will remain healthy and develop a latent TB infection (LTBI). Biomarkers to differentiate aTB from LTBI in children, especially in very young children, are urgently needed. To identify M. tuberculosis-specific functional T cell subsets related to clinical manifestations in children, we enrolled 87 children exposed to M. tuberculosis. After standard clinical assessment, the children were classified as aTB, LTBI, or uninfected. Their CD4+T cell cytokine profiles (IFN-γ, TNF-α, IL-2, IL-17) were analyzed at the single-cell level by flow cytometry after stimulation with 3 mycobacterial antigens, purified protein derivative, early-secreted-antigen target-6 (ESAT-6), or heparin-binding haemagglutinin (HBHA). This approach identified age-related discriminative markers between aTB and LTBI. Whereas among the 3 to 15 years-old children, an excellent discrimination between aTB and LTBI was provided by comparing the ratio between the proportions of ESAT-6-induced IFN-single+ and ESAT-6-induced TNF-single + CD4+ T lymphocytes, this was not the case for children younger than 3 years. In contrast in this group (< 3 years), the analysis of HBHA-induced IL-17single+ CD4+ T lymphocytes allowed us to identify children with LTBI by the high proportion of this cellular lymphocyte subset, whereas this was not the case for children with aTB. The analysis at the single-cell level of T cell immune responses induced by mycobacterial antigens are thus different in infected children younger or older than 3 years of age. HBHA-induced IL-17 production by CD4+ T lymphocytes was associated with protection only in children under 3 years who are at high risk for rapid progression to aTB. This suggests that the HBHA-induced IL-17 production by CD4+ T lymphocytes is a potential new correlate of protection against M. tuberculosis in humans, and that the distinction between children with LTBI and those with aTB is possible based on age-related diagnostic markers